Determinants of Malnutrition Among Children Aged 0 to 59 months: A Study at the Bonassama District Hospital, Douala, Cameroon - Godfroy Rostant Pokam Djoko; Murielle Tsobgny Nguefack; Devis Sobnang (Public Health Frontier, 2026)
Malnutrition is a major cause of childhood morbidity and mortality, affecting children’s growth and development. This study aimed to identify the factors associated with malnutrition among children aged 0 to 59 months at Bonassama District Hospital in Douala. A descriptive and analytical cross-sectional study was conducted from July 2025 to April 2026 among children aged 0 to 59 months seen in the pediatrics and immunization units. Data were collected using a questionnaire administered to parents. Nutritional status was assessed according to WHO standards, and associated factors were identified through multivariate analysis. Among the children studied, 82.2% had normal nutritional status and 17.8% were malnourished. After adjustment, the factors significantly associated with malnutrition were type of housing (modern house: AOR = 2.10; 95% CI: 1.03–4.01; p = 0.044), tenant status (AOR = 3.01; 95% CI: 1.53–6.78; p < 0.001), history of respiratory infection (AOR = 2.12; 95% CI: 1.20–5.35; p = 0.019), and occasional use of health services (AOR = 2.23; 95% CI: 1.05–5.21; p = 0.030). Mothers’ knowledge of essential food groups was not significantly associated with malnutrition. Malnutrition remains a significant problem among children under five years of age in Bonassama. Prevention strategies should incorporate health, socioeconomic, and environmental factors to improve screening and management of at-risk children.